Beckman/Spinco Model 153 Microtitrator
A microtitrator is an instrument designed to titrate very small volumes of liquid. This model is shown with a Microfuge centrifuge and other accessories.
Keywords: Beckman Instruments, Inc. Spinco Division; Scientific apparatus and instruments; Volumetric analysis; Centrifuges; Beckman Instruments, Inc.